2020
DOI: 10.32493/jpkpk.v3i2.4520
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Dampak Digital Banking Dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada Sebuah Bank Swasta

Abstract: ABSTRAKAbstrak. Penelitian ini memiliki tujuan untuk menganalisa dampak dari Digital Banking dan Kualitas Pelayanan terhadap Kepuasan Nasabah pada PT. Bank OCBC NISP, Tbk. Jenis penelitian kuantitatif dengan jumlah sampel 100 orang responden yang merupakan nasabah PT. Bank OCBC NISP, Tbk. Data diumpulkan melalui wawancara kuisioner. Data dianalisa menggunakan uji hipotesis. Pengujian yang telah dilakukan menghasilkan adanya pengaruh digital banking dan kualitas pelayanan secara bersama-sama terhadap kepuasan n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Muzdalipah and Mahmudi (2023) also revealed that mobile banking service capabilities, ease of use, and customer reliability attract consumers interested in using mobile banking as a medium for conducting Islamic banking transactions, especially among millennials. Research related to digital banking was also conducted by Sicillia and Yazid (2020), who uncovered that digital banking and service quality variables positively and significantly affect customer satisfaction. Similar results were obtained by Pranantha (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Muzdalipah and Mahmudi (2023) also revealed that mobile banking service capabilities, ease of use, and customer reliability attract consumers interested in using mobile banking as a medium for conducting Islamic banking transactions, especially among millennials. Research related to digital banking was also conducted by Sicillia and Yazid (2020), who uncovered that digital banking and service quality variables positively and significantly affect customer satisfaction. Similar results were obtained by Pranantha (2021).…”
Section: Introductionmentioning
confidence: 99%